Konstruk Media Pembelajaran Baamboozle Pada SD Islam Sinar Cendekia - Winaningsih, Elis Tuti; Syarif, Fajar (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
This research explores the use of gamification in learning, especially the use of the Baamboozle platform. This is related to the role of PAI teachers in increasing students' learning motivation, especially in grade 5 at Sinar Scholar Islamic Elementary School. The aim of this research is to analyze teacher strategies in increasing student learning motivation in PAI classes. This research agrees with research entitled "Teacher Strategies in Increasing Student Learning Motivation in Islamic Religious Education Subjects" written by Alif Achadah which states that teachers must have ideal strategies in teaching according to different conditions at each level so that students are motivated to learn. can increase. This research uses a type of qualitative research in the form of field research. The research method uses a descriptive analysis model with a sociological and psychological approach. Research data sources consist of primary data sources including interviews with related parties, documentation collection, observation, triangulation, and secondary data sources secondary data obtained from all written data relevant to the research topic. Data analysis uses Miles and Huberman theory, starting from collecting data, reducing data, presenting data, drawing conclusions, and validating data. This research presents the conclusion that the implementation of active learning through the Baamboozle platform used in PAI subjects in class V of Sinar Scholar Islamic Elementary School is in accordance with the RPP and is considered effective in increasing students' learning motivation.